Nine Unique Iridoids and Iridoid Glycosides From Patrinia scabiosaefolia - Liu, Zhenhua; Niu, Yun; Zhou, Li; Meng, Lijun; Chen, Sitan; Wang, Mengke; Hu, Jiangmiao; Kang, Wenyi (Frontiers in Chemistry, 2021)
Patrinia scabiosaefolia is a medical and edible Chinese herb with high nutritional and medicinal value. In the continuing study of its chemical constituents led to find nine unique iridoids and iridoid glycosides, including three new iridoids (1-3) and six previously unknown irioid glycosides (5-10), and one known compound (4). Among them, compound 1 was a deformed iridoid, while compounds 3, 5-7, and 10 formed a new ring in their skeletons which was uncommon in this genus. For compound 3, the new ring existed between C-3 and C-10, while a 1,3-dioxane appeared between C-7 and C-10 in compounds 5-7, and 10. Moreover, compound 10 was a bis-iridoid glycoside, which were the first reported in P. scabiosaefolia. And the sugar of irioid glycosides (5-10) was glucose at C-11 except 9 with a 5-deoxyglucose moiety. All their structures were confirmed based on the extensive spectroscopic analysis, including IR, UV, HR-ESI-MS, ECD, and 1D- and 2D-NMR experiments. And their cytotoxic activities against HL-60, A-549, SMMC-7721, MCF-7, SW480 were tested.